If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15=-6(4x-7)-3(-7+8x)
We move all terms to the left:
15-(-6(4x-7)-3(-7+8x))=0
We add all the numbers together, and all the variables
-(-6(4x-7)-3(8x-7))+15=0
We calculate terms in parentheses: -(-6(4x-7)-3(8x-7)), so:We get rid of parentheses
-6(4x-7)-3(8x-7)
We multiply parentheses
-24x-24x+42+21
We add all the numbers together, and all the variables
-48x+63
Back to the equation:
-(-48x+63)
48x-63+15=0
We add all the numbers together, and all the variables
48x-48=0
We move all terms containing x to the left, all other terms to the right
48x=48
x=48/48
x=1
| u-3/4=41/2 | | 3(2x-4)+4x=3x-7+5x | | (x−2)=−(5−x) | | f-15/5=10 | | 3x+17+x=7x+10 | | 10.50+4.25b=31.75 | | 3000+100x=5400+70 | | -16=-15/16(4q/5q+32/4) | | 3d/2-3=d | | 5(x-12)=0.5(4x+6) | | 3.4x=61.2 | | -4.12+0.2x=2.1x-0.7 | | 6x-40+60=180 | | -5p+80=3p | | -5(x-3)=-5x-3 | | -5/8v=-10 | | 7x-9+5x-1=9x+1 | | 1/3x-8=-18 | | 11+5=-2(8x-8) | | 6x-40+60+x=180 | | 8r-4=6r+12 | | 6/x/2=4 | | 7+5c=-3+3c | | 3w+5=2w+w-7 | | 2-8(-5+3n)=34 | | .x+25=12 | | 52+43+x=10 | | -2.5=17.1+y/6 | | 30=7g-5 | | -u=2 | | t+18/5=17/4 | | 7x-9-5x-1=9x+1 |